2015 IEEE 23rd International Conference on Program Comprehension 2015
DOI: 10.1109/icpc.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Make It Simple - An Empirical Analysis of GNU Make Feature Use in Open Source Projects

Abstract: Abstract-Make is one of the oldest build technologies and is still widely used today, whether by manually writing Makefiles, or by generating them using tools like Autotools and CMake. Despite its conceptual simplicity, modern Make implementations such as GNU Make have become very complex languages, featuring functions, macros, lazy variable assignments and (in GNU Make 4.0) the Guile embedded scripting language. Since we are interested in understanding how widespread such complex language features are, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Callaú et al [25] conducted an empirical study on the use of the reflection feature in 1000 Smalltalk projects by statically tracing the features being used from the AST of the source code. Martin et al [26] examined the use of GNU Make's language features (such as functions, macros, lazy variable assignments and the Guile embedded scripting language) in around 12k make files of 250 open source projects. They used TXL to define a custom grammar for Makefiles to extract and count instances of features.…”
Section: Related Workmentioning
confidence: 99%
“…Callaú et al [25] conducted an empirical study on the use of the reflection feature in 1000 Smalltalk projects by statically tracing the features being used from the AST of the source code. Martin et al [26] examined the use of GNU Make's language features (such as functions, macros, lazy variable assignments and the Guile embedded scripting language) in around 12k make files of 250 open source projects. They used TXL to define a custom grammar for Makefiles to extract and count instances of features.…”
Section: Related Workmentioning
confidence: 99%
“…Adams et al [18,19] and S.McIntosh et al [34] have shown how build systems continue to grow in size and complexity. Martin et al [32,33] work focused specifically on Makefiles and shed light on the complexity associated with maintaining Makefiles due to the various features and constructs utilized within them. Seo et al [39] studied builds at Google and stated that up to 37% of their build failed, mostly due to neglected build maintenance.…”
Section: Related Workmentioning
confidence: 99%